PERANAN PUPUK CAIR ASAL INOKULAN Trichoderma sp PADA BUDIDAYA TANAMAN KENTANG MERAH SEMI ORGANIK - Jamilah Jamilah; Pendra Fauzi; Aslan Sari Thesiwati (Jurusan Tanah Fakultas Pertanian Universitas Andalas, 2022)
The demand for red potatoes is quite high, especially for supermarkets and culinary businesses that require potatoes as the basic ingredient. To achieve optimal potato production, it is necessary to provide sufficient fertilizer, while the price of artificial fertilizers is getting more expensive, therefore it is necessary to look for alternative low-cost fertilizers. The purpose of the study was to find out the benefits of Trichoderma sp. fungi as liquid organic fertilizer (POC), in an effort to diminish the use of artificial fertilizers towards organic potato cultivation. The experiment was carried out from June - September 2021 at Danau Kembar. This experiment was arranged in a completely randomized design (CRD), with 2 treatment factors and 3 replications. The first factor was the administration of POC Derma (fermented inoculant Trichoderma sp) doses consisting of 5 levels, namely: 0 ml L-1 (D0), 25 ml L-1 (D1), 50 ml L-1 (D2), 75 ml L-1 (D3), 100 ml L-1 (D4). The second factor the intensity of the application consists of two levels: (I1) 1 time a week and (I2) once every 2 weeks. Observational data were analyzed by means of variance using the F-test with a significant level of 5% and if the treatment had a significant effect, it was continued with the Least Significant Difference (BNT) test with a level of 5%. From the results of experiments that have been carried out, it is found that giving POC Derma (fermented inoculant Trichoderma sp) 75 ml L-1 inevery 2 weeks gave the highest production reaching 27.56 t ha-1 in semi-organic red potato cultivation.Key words: Derma liquid organic fertilizer, Trichoderma sp, red potato, semi organic